EXPLORING STUDENTS' PERCEPTIONS OF PODCAST-BASED READING TASKS IN ENHANCING READING SKILLS - Adi, Adi; Setiyo Astuti, Endang; Suhartatik, Suhartatik; Jasuli, Jasuli (LPPM STBA Pontianak, 2025)
This study explores students' perceptions of podcast-based reading tasks in enhancing reading skills among fourth-semester English Department students at a private university in Malang. Using a qualitative case study approach, twelve intermediate-level students participated in podcast-based reading activities, followed by semi-structured interviews. The collected data were transcribed and analyzed using thematic analysis to identify recurring patterns in students’ experiences. The findings reveal that students experienced improved reading comprehension when listening to podcasts before reading transcripts, particularly in initial text understanding, word recognition, attention to textual details, and active engagement with intentionally gapped transcripts. Despite minor challenges related to speech clarity, students reported increased reading confidence and expressed interest in continued use of this method. The integration of listening and reading through podcasts demonstrates potential for enhancing EFL students’ reading development and engagement with English texts.